Oxidative Coupling of Methane: Examining the Inactivity of the MnOx‐Na2WO4/SiO2 Catalyst at Low Temperature. (28th February 2022) - Si, Jiaqi; Zhao, Guofeng; Sun, Weidong; Liu, Jincun; Guan, Cairu; Yang, Yong; Shi, Xue‐Rong; Lu, Yong
Abstract: Oxidative coupling of methane (OCM) catalyzed by MnO x ‐Na2 WO4 /SiO2 has great industrial promise to convert methane directly to C2–3 products, but its high light‐off temperature is the most challenging obstacle to commercialization and its working mechanism is still a mystery. We report the discovery of a low‐temperature active and selective MnO x ‐Na2 WO4 /SiO2 catalyst enriched with Q 2 units in the SiO2 carrier, being capable of converting 23 % CH4 with 72 % C2–3 selectivity at 660 °C. From experiments and theoretical calculations, a large number of Q 2 units in the MnO x ‐Na2 WO4 /SiO2 catalyst is a trigger for markedly lowering the light‐off temperature of the Mn 3+ ↔Mn 2+ redox cycle involved in the OCM reaction because of the easy formation of MnSiO3 . Notably, the MnSiO3 formation proceeds merely through the SiO2 ‐involved reaction in the presence of Na2 WO4 : Mn7 SiO12 +6 SiO2 ↔7 MnSiO3 +1.5 O2 . The Na2 WO4 not only drives the light‐off of this cycle but also gets it working with substantial selectivity toward C2–3 products. Our findings shine a light on the rational design of more advanced MnO x ‐Na2 WO4 based OCM catalysts through establishing new Mn 3+ ↔Mn 2+ redox cycles with lowered light‐off temperature. Abstract : For the oxidative coupling of methane (OCM) reaction, the MnO x ‐Na2 WO4 /SiO2 catalyst enriched with Q 2 units in the SiO2 carrier achieves 23 % CH4 conversion and 72 % C2–3 selectivity at 660 °C. A large number of Q 2 units in MnO x ‐Na2 WO4 /SiO2 is a trigger for markedly lowering the light‐off temperature of the Mn 3+ ↔Mn 2+ redox cycle because of the easy formation of MnSiO3 .